2019
DOI: 10.1021/acs.iecr.9b04744
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Analysis of Postcombustion Hydrate-Based CO2 Capture with Tetrahydrofuran and Tetra-n-butylammonium Bromide

Abstract: Hydrate-based gas separation (HBGS) is a novel carbon dioxide capture technology, which helps in the alleviation of the human-induced global warming crisis. However, hydrate formation for flue gases with relatively low CO2 concentration requires higher pressures or lower temperatures. The addition of thermodynamic and kinetic promoters seems to be the most efficient way of moderating the hydrate formation condition. In this research, a two-stage hydrate-based CO2 capture process was proposed and then simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…However, the weakly selective gas can also form hydrates, resulting in the lower selectivity of hydrate-based gas separation (HBGS) . In addition, HBGS requires separation operations at higher pressures, while some studies , have indicated that the compression energy consumption accounts for more than 50% of the total technological energy. Therefore, more in-depth research is needed to improve the mild experimental condition and separation selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the weakly selective gas can also form hydrates, resulting in the lower selectivity of hydrate-based gas separation (HBGS) . In addition, HBGS requires separation operations at higher pressures, while some studies , have indicated that the compression energy consumption accounts for more than 50% of the total technological energy. Therefore, more in-depth research is needed to improve the mild experimental condition and separation selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the rapid increase of global energy demand, NGH is considered to be a new and potential energy on account of its enormous energy reserves . At present, various innovative technologies related to NGH have been developed for industrial applications, such as water desalination, energy storage and transportation, , gas separations, , and CO 2 capture and storage …”
Section: Introductionmentioning
confidence: 99%
“…6 At present, various innovative technologies related to NGH have been developed for industrial applications, such as water desalination, 7 energy storage and transportation, 8,9 gas separations, 2,10 and CO 2 capture and storage. 11 To realize the commercial extraction of natural gas from hydrate deposits in the future, a variety of exploitation methods have been proposed. The depressurization method, 12 in which the reservoir pressure is reduced below the hydrate equilibrium pressure, is generally acclaimed as the most effective one because of its simple technical requirements and high energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xie et al evaluated the effect of hydrate promoters on the energy consumption in the hydrate-based CO 2 capture process. In their recent study, they implied that energy consumption for the hydrate-based CO 2 capture process is higher than energy consumption for the MEA-based absorption process . In the processes designed by Tajima et al and Xie et al for post-combustion CO 2 capture, it was assumed that CO 2 recovery for each hydrate formation stage is 0.95, while the experimental studies show that actual CO 2 recovery for a single hydrate formation stage is much lower than 0.95.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent study, they implied that energy consumption for the hydrate-based CO 2 capture process is higher than energy consumption for the MEAbased absorption process. 17 In the processes designed by Tajima et al 15 and Xie et al 16 for post-combustion CO 2 capture, it was assumed that CO 2 recovery for each hydrate formation stage is 0.95, while the experimental studies show that actual CO 2 recovery for a single hydrate formation stage is much lower than 0.95. Accordingly, the standalone hydrate formation CO 2 capture process to meet the CO 2 capture plants criteria (at least 90% of CO 2 captured with purity more than 95 mol %) is not sufficient.…”
Section: Introductionmentioning
confidence: 99%